PERLUASAN MAKNA ASAS LEGALITAS DALAM RANCANGAN KITAB UNDANG-UNDANG HUKUM PIDANA JIKA DIBANDINGKAN DENGAN KONSEP DELIK PERZINAAN DALAM KITAB UNDANG- UNDANG HUKUM PIDANA - Nst, Habi Afpandi; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The principle of legality is a fundamental principle and is very important in criminal law provisions. This principle is intended to protect the public from abuse of authority or in this case the lawmakers, stated in Article 1 paragraph 1 of the Code of Penal. An act can be held responsible if a criminal act has been stipulated in the Criminal Justice Act.In the Application of the offense of adultery according to the Code of Penal is a fornication are men and women that one or both are tied to marriage do mistress (overspel), or men and women who should suspect that involved in the act that has been committed to marriage legitimate.Meanwhile fornication applicable based on the values in society is every act of intercourse between men and women outside of his marriage. In other words fornication prevailing element in the wider community of the elements of fornication provided for in the Criminal Justice Act. However, although fornication prevailing in the wider community, as a consequence of the absolute legality principle set out in Article 1 paragraph 1 of the Code of Penal such actions shall not be accountable if it does not correspond to the elements loaded in Article 284 of the Book of the Law Criminal law.The setting of adultery in the draft Penal Code is a regulation fornication based on the values that live in Dutch society used to be, because the draft Penal Code is a relic of the Netherlands as a country that once colonized Indonesia and It is causing acts of vigilantism by the surrounding community, because the community considers the act is an act that violates the values prevailing in society. Because the values that live in a different society with the values that form the basis of making the Code of Penal who is of Dutch heritage.Keywords: Adultery-Fornication-rinciple of Legality